Penerapan Metode Enterprise Architecture Planning dalam Pengembangan Kelestarian Alam TNWK Lampung - Hilda Dwi Yunita; Triyugo Winarko (Universitas Bandar Lampung (UBL), 2022)
Way Kambas National Park in Lampung is a National Park in which there are various kinds of flora and fauna that must be preserved, the most popular of which is the elephant. The problem faced by the Way Kambas National Park Center is that it does not yet have optimal technology and does not yet have a clear plan in developing its technological infrastructure so that the provision of information or exchange of data regarding flora and fauna is experiencing problems and the development of natural sustainability is only based on the needs at that time. not necessarily have optimal value and benefits. Therefore it is necessary to use the right method for its development. In this study the method used is the Enterprise Architecture Planning method which is applied in the form of a Blueprint. This blueprint can be used to support the policy strategies taken by the management in taking steps to develop natural sustainability related to information and technology. The purpose of this study is to analyze threats or causes that can damage the natural sustainability of Way Kambas National Park, analyze data, architecture and technology used in Way Kambas National Park management and to develop the natural preservation of Way Kambas National Park by using better technology so that sustainability nature can be well preserved without overriding the tourist attraction. The result of this research is to produce an information architecture picture (blueprint) both from data architecture, application and technology which is expected to be used as a basis for the development of information systems in Way Kambas National Park.